Factor V Leiden Mutation–Related Chronic Skin Ulcers. (March 2013) - Kayatas, Kadir; Cebeci, Filiz; Karatoprak, Cumali; Benzer, Muhammet; Demirtunç, Refik; Demirkesen, Cuyan
Chronic skin ulcers require extensive, systemic differential diagnosis; thus, they are difficult to diagnose and treat. Transient or persistent hypercoagulable states are among the rare causes of skin ulcers. Here, we present the case of a 27-year-old woman patient with recurrent, nonhealing skin ulcers of 8 years' duration, who had been treated unsuccessfully with various medications under different diagnoses at different clinics. On admission, a skin biopsy demonstrated occlusive vasculopathy, and the search for an inherited hypercoagulable state revealed a heterozygous factor V Leiden mutation. The patient was treated with anticoagulants and hyperbaric oxygen. On treatment, the skin lesions healed and did not recur.